Anti-inflammatory and Anti-allergic Effects of Salvigenin in an Ovalbumin-Induced Allergic Rhinitis in Mice - Gong, Nan; Chang, Huimin; He, Mengchao; Zhang, Xiaohong; Li, Wenjing (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Allergic Rhinitis (AR) is a prevalent inflammatory disorder of the nasal mucosa, often triggered by an IgE-mediated immune reaction to allergens. The underlying cause of AR can be attributed to the genetic predisposition and environmental causes that trigger an aberrant immune response. Objectives: The present work was performed to understand the salutary roles of salvigenin against allergen-initiated AR in mice. Materials and Methods: AR was initiated in BALB/c mice by intraperitoneally administering Ovalbumin (OVA) at a dose of 50 µg along with aluminum hydroxide. The salvigenin was administered at 10 and 20 mg/kg concentrations, respectively. The analyses of nasal symptoms (nasal rubbings and sneezing) were performed on the final day of OVA challenge. The histamine and allergen-specific IgE in the experimental mice were assessed using kits. Mouse airways Smooth Muscle Cells (SMCs) were extracted and sensitized with 20 µL OVA in vitro. Subsequently, they were treated with 10 and 20 mg/kg of salvigenin. The concentrations of pro-inflammatory cytokines were assessed in the experimental mice as well as OVA-induced SMCs using commercial assay kits. The commercial assay kits were employed for the analysis of oxidative stress biomarkers in the OVA-induced SMCs. Results: The treatment of salvigenin to the mice with AR was demonstrated a substantial diminution in nasal rubbings and sneezing incidences. In AR mice, salvigenin successfully diminished the levels of histone, allergen-specific IgE, eosinophils and inflammatory markers in the AR mice. The MDA and ROS were diminished, while the SOD was elevated in the OVA-challenged SMCs after the salvigenin treatment. The inflammatory cytokines were reduced in the OVA-challenged SMCs after the salvigenin treatment. Conclusion: The current results proved that salvigenin effectively decreased inflammatory and allergic reactions in the mice with OVA-induced AR. These outcomes highlight that salvigenin may be a talented salutary agent for treating AR.
Keywords: Allergic diseases; Histamine; Inflammation; Malondiadehyde; Salvigenin